Description of Cohnella rhizoplanae sp. nov., isolated from the root surface of soybean (Glycine max) - Kämpfer, Peter; Glaeser, Stefanie P.; McInroy, John A.; Busse, Hans-Jürgen; Clermont, Dominique; Criscuolo, Alexis; Justus Liebig University Giessen (My University, 2025)
A Gram-staining-positive, aerobic bacterium, designated strain JJ-181T, was isolated from the root surface of soybean. Based on the 16S rRNA gene sequence similarities, strain JJ-181T was grouped into the genus Cohnella, most closely related to Cohnella hashimotonis F6_2S_P_1T (98.85%) and C. ginsengisoli GR21-5T (98.3%). The pairwise average nucleotide identity and digital DNA-DNA hybridisation values of the JJ-181T genome assembly against publicly available Cohnella type strain genomes were below 84% and 28%, respectively. The fatty acid profile from whole cell hydrolysates, the cell wall diaminoacid, the quinone system, the polar lipid profile, and the polyamine pattern supported the allocation of strain JJ-181T to the genus Cohnella. In addition, the results of physiological and biochemical tests also allowed phenotypic differentiation of strain JJ-181T from its closely-related Cohnella species. Functional analysis revealed that strain JJ-181T has different gene clusters related to swarming motility, chemotaxis ability, and endospore and biofilm formations. The gene content also suggests the ability of strain JJ-181T to synthesise biotin and riboflavin, as well as indole-3-acetic acid, an important phytohormone for plant growth. Based on polyphasic analyses, strain JJ-181T can be classified as a new species of the genus Cohnella, for which we propose the name Cohnella rhizoplanae sp. nov., with strain JJ-181T (= LMG 31678T= CIP 112018T = CCM 9031T = DSM 110650T) as the type strain.
Keywords: ddc:630